When the Stepfather Crosses the Line: The Unheard Voices of Abused Stepchildren - Ryzza Banila; Rain Kazmyr Aquino; Princess Elizabeth Arañez; Kirsten Loui Bande; Gierzel Marie Baybay; Nhesa Marie Tercero (RSF Press, 2026)
This qualitative study examines the lived experiences of stepchildren who have experienced sexual harassment perpetrated by their stepfather. Sexual harassment is defined as any unwelcome sexual behavior—verbal, nonverbal, or physical—that can cause severe emotional and psychological harm, particularly when it occurs within the family context. Using Interpretative Phenomenological Analysis (IPA), five (5) participants aged 18 years old and above were selected through purposive sampling. In-depth semi-structured interviews were conducted to gather detailed personal narratives. The study revealed five (5) emergent themes: Abuse Consequences, which refer to the emotional, psychological, and relational effects resulting from abuse; Trauma Impact, which describes the enduring psychological distress and disruption in daily functioning caused by traumatic experiences; Trauma-Driven Fear, which reflects persistent fear, hypervigilance, and mistrust rooted in betrayal by a caregiver; Maladaptive Coping Strategies, which involve unhealthy or ineffective ways of coping such as avoidance, emotional withdrawal, and self-blame; and Impact and Identity, which captures how the experience shaped participants’ self-concept, self-worth, and identity development. These findings are supported by Trauma Theory and Betrayal Trauma Theory, which explain how trauma develops and how individuals respond to traumatic events, particularly when the perpetrator is a trusted family member. Overall, this study highlights the profound emotional and psychological impact of familial sexual harassment, the coping mechanisms adopted by survivors, and the insights they provide for future readers and researchers. The study emphasizes the importance of understanding familial sexual harassment, increasing awareness, and supporting self-development and healing among survivors.